Strategi coping pada mahasiswi korban perceraian orangtua - Anastacia, Katarina Diva; Setiawan, Antonius Ian Bayu (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Individuals need to develop coping strategies to overcome feelings, express emotions, and find strategies to deal with parental divorce situations. The purpose of this study was to determine the coping strategies used by female students in dealing with parental divorce that occurred in their lives and to determine the factors that influence female students in taking these coping strategies. The method in this study was qualitative and the research design was phenomenology. The subjects in this study were students aged 20–25 who experienced parental divorce, totaling four people. Data collection by conducting interviews. The data analysis techniques used were making interview transcripts, conducting data reduction, coding processes, and drawing conclusions from the data that had been collected. The results of the study showed that the coping strategies used by subjects who experienced parental divorce were problem-focused coping strategies, emotion-focused coping strategies, and acceptance. Then, in carrying out these coping strategies, individuals are influenced by factors, including physical condition factors, positive views, social support, and material.